2015
DOI: 10.2174/1874149501509010622
|View full text |Cite
|
Sign up to set email alerts
|

Damping Prediction Technique of the Bolted Joint Structure Considering Pretension Force

Abstract: Abstract:At the initial phase of the mechanical product development, it is very important to effectively obtain the modal damping ratio of the bolted joint structure for accurately predicting dynamic response. The energy dissipation has been estimated using a finite element model incorporating the effect of pretension force of the bolted joint. First, the modal damping ratios of the first four modes are extracted by experimental method. Secondly, the lap joint finite element model with pretension force paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The pyroshock is attenuated as it travels through these structures, and the propagation characteristics can vary depending on the bolt load. Previous studies have shown that as the bolt load increases, the connection strength between the structures increases, resulting in higher natural frequencies and lower damping ratios due to increased stiffness (Xu and Hess, 2013; Sun and Liao, 2015; Kulkarni and Kulkarni, 2017). Therefore, the magnitude of the shock passing through bolted structures is expected to increase.…”
Section: Introductionmentioning
confidence: 99%
“…The pyroshock is attenuated as it travels through these structures, and the propagation characteristics can vary depending on the bolt load. Previous studies have shown that as the bolt load increases, the connection strength between the structures increases, resulting in higher natural frequencies and lower damping ratios due to increased stiffness (Xu and Hess, 2013; Sun and Liao, 2015; Kulkarni and Kulkarni, 2017). Therefore, the magnitude of the shock passing through bolted structures is expected to increase.…”
Section: Introductionmentioning
confidence: 99%